Breslow density ability to predict melanoma survival: should it be used in clinical practice? - Gil-Pallares, Pedro; Figueroa-Silva, Olalla; Taboada-Paz, Laura; Gil-Pallares, María Eugenia; Sánchez-Aguilar Rojas, María Dolores; Balboa-Barreiro, Vanesa; Navarro-Bielsa, Alba; Suárez-Peñaranda, José Manuel (Clinical and experimental dermatology, 2024)
Breslow density (BD) is an estimation of melanoma volume, which has emerged as a novel histopathological prognostic biomarker. To evaluate the role of BD as a predictor of patients' survival and assess its prognostic value in relation to overall survival (OS), disease-free survival (DFS), melanoma-specific survival (MSS) and metastasis-free survival (MFS). A retrospective observational study in a cohort of 107 patients with invasive melanoma was conducted. Kaplan-Meier and Log-rank tests were used for 10-year survival analysis. The ability of BD and Breslow thickness (BT) to predict survival was assessed using receiver operating characteristic curves. The average follow-up was 115 months, excluding deaths. People with BD ≥ 65% showed lower survival rates compared with the BD < 65% group (log-rank test P < 0.001). Area under the curve (AUC) of BD ≥ 65% was higher than BTs for all studied survival rates except for MSS, in which absolute BD showed the highest value. BD is proposed as a simple, valuable and inexpensive histopathological feature that could provide additional valuable information to that available from melanoma staging, as it has proved to have a statistically significant prognostic value in relation to survival in patients with melanoma and comparable 10-year survival prediction ability with that of BT.